5G Radio Access Network Architecture Based on C-RAN - Qiuyan Lei; Zhizhong Zhang; Fang Cheng; Haonan Hu (Dianxin kexue)
Based on the analysis of the traditional cellular structure of the radio access network（RAN）which is facing more and more challenges, the development trend and demand of current mobile communication system were introduced, and the research goal and requirement for the fifth generation mobile communication system（5G）were analyzed. Aiming at solving this problem, a new type of radio access network architecture based on C-RAN was proposed. Moreover, the potential key technologies were illustrated in detail, including UDN, virtualization（software defined network and network function virtualization）, CDN and green communication. Those provide reference for 5G access network architecture research.